A Brief Military History of the Later Reign of Šāpur II - JACKSON BONNER, Michael Richard (Historia i Świat, 2017)
This is a brief history of the wars of Šāpur II from the middle of the fourth century to the death of that king in the year 379. These conflicts represent the military operations of the Sasanid state at its height before a gradual decline under the successor to Šāpur II.